Family Conflicts in Bawang Putih and Bawang Merah Movie: A Feminist Perspective - Supandi, Dwika Putri; Herlyna, Herlyna; Mujani, Sahril (STIBA IEC JAKARTA, 2025)
Although family conflict is frequently depicted in folktale-based films, there is still little feminist literary analysis of it in Indonesian literary studies. This study aims to rectify this deficiency through looking at gender roles and family conflict in the film Bawang Putih dan Bawang Merah, which draws inspiration from traditional Indonesian folklore. Finding out how patriarchal values are ingrained in family dynamics and how women are oppressed and empowered is the goal of this study. Characters, dialogue, conflict patterns, and narrative structure are all examined in this study using feminist literary theory and a qualitative descriptive methodology. The findings demonstrate how the movie depicts unfairness, favouritism, jealousy, and power disparity among female characters in a patriarchal household. The motion picture. The film also emphasises the female characters' strong and defiant moments, highlighting the intricate relationship between feminist views and conventional values. The analysis comes to the conclusion that although the film perpetuates certain gender stereotypes, its narrative decisions also offer chances for feminist discourse